Does Context Matter? A Multi-Method Assessment of Affect in Adolescent Depression Across Multiple Affective Interaction Contexts. (March 2017) - Nelson, Benjamin W.; Byrne, Michelle L.; Sheeber, Lisa; Allen, Nicholas B.
This study utilized a multimethod approach (self-reported affect, observed behavior, and psychophysiology) to investigate differences between clinically depressed and nondepressed adolescents across three different affective interaction contexts with their parents. A total of 152 adolescents (52 males, 14–18 years old), and their parents, participated in a laboratory session in which they discussed positive and negative aspects of their relationship and reminisced on positive and negative memories. We found that across contexts depressed adolescents exhibited higher negative affect and behaviors, lower positive behaviors, and greater autonomic and sympathetic activity. Context-specific findings indicated that (a) depressed adolescents exhibited greater persistence of negative affect and dysphoric behavior across the sequence of tasks, whereas these phenomena declined among their nondepressed peers; (b) depressed adolescents had greater increases in aggressive behaviors during negative interactions; and (c) depressed adolescents had greater parasympathetic withdrawal during negative interactions, whereas this response characterized the nondepressed group during positive interactions.